The Invention of Palestinian Citizenship, 1918-1947 - Banko, Lauren (Edinburgh University Press, 2016)
Explores the colonial, social and political history of the creation of citizenship in mandate Palestine In the two decades after the First World War, nationality and citizenship in Palestine became less like abstract concepts for the Arab population and more like meaningful statuses integrated into political, social and civil life and as markers of civic identity in a changing society. This book situates the evolution of citizenship at the centre of state formation under the quasi-colonial mandate administration in Palestine. It emphasises the ways in which British officials crafted citizenship to be separate from nationality based on prior colonial legislation elsewhere, a view of the territory as divided communally, and the need to offer Jewish immigrants the easiest path to acquisition of Palestinian citizenship in order to uphold the mandate's policy. In parallel, the book examines the reactions of the Arab population to their new status. It argues that the Arabs relied heavily on their pre-war experience as nationals of the Ottoman Empire to negotiate the definitions and meanings of mandate citizenship. Key features Covers the overlapping social, administrative and political eras in the creation of Palestinian citizenship, from the final decades of the Ottoman imperial age through the first two decades of the mandate Explores a transitional period in Palestine's history that has seen little nuanced historical research Places the development of the changing status of citizenship in mandate Palestine in its historical context Approaches the 'invention' of citizenship in Palestine through a number of frameworks: the wider British imperial project, the development of Arab populist politics and civil society, and the circulation of ideas to and from the Palestinian Arab diaspora Incorporates a number of under-used and un-used Arabic press and other documentary sources